Characterizing distinct profiles of immune and inflammatory response with age to Omicron infection - Zhang, Lina; Wang, Zhanwen; Lyu, Feng; Liu, Chun; Li, Chunhui; Liu, Wei; Ma, Xinhua; Zhou, Jieyu; Qian, Xinyu; Qian, Zhaoxin; Lu, Yong (Frontiers in Immunology, 2023)
Background Understanding inflammatory and immune responses to Omicron infection based on age is crucial when addressing this global health threat. However, the lacking of comprehensive elucidation hinders the development of distinct treatments tailored to different age populations. Methods 1299 cases of Omicron infection in Shanghai were enrolled between April 10, 2022 and June 3, 2022, dividing into three groups by ages: Adult group (18-59 years), Old group (60-79 years), and Elder group (≥ 80 years). Laboratory data including inflammatory cytokines, cellular, and humoral immunity were collected and analyzed. Results The mean age of Adult, Old, and Elder groups were 44.14, 69.98, and 89.35 years, respectively, with 40.9% being men. The Elder group patients exhibited higher white blood cell (WBC) counts and elevated levels of inflammatory cytokines, but their lymphocyte counts were relatively lower. In comparison to the Old group patients, the Elder group patients demonstrated significantly lower CD3+ T-cell counts, CD3+ T-cell proportion, CD4+ T-cell counts, CD8+ T-cell counts, and CD19+ B-cell counts, while the NK-cell counts were higher. Omicron negative patients displayed a higher proportion of CD19+ B-cells and higher levels of Complement-3 and IL-17 compared to the positive patients in the Old group. Omicron negative patients had lower WBC counts, CD3+CD8+ T-cells proportion, and the levels of serum amyloid A and IgA in the Elder group, but the CD4+/CD8+ ratio was higher. Conclusions Our study identified the distinct profiles of inflammatory and immune responses to Omicron infection varying with age and highlighted the diverse correlations between the levels of various biomarkers and Omicron infected/convalescent patients.